2023
DOI: 10.21608/ejnsr.2023.277896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Awareness Program Regarding Climate Change on Knowledge, Attitudes and Practices of University Students

Abstract: Climate change is impacting human lives and health in a variety of ways. It threatens the essential ingredients of good health as; clean air, safe drinking water, nutritious food supply and safe shelter and has the potential to undermine decades of progress in global health. Aim: To evaluate the effect of awareness program regarding climate change on knowledge, attitude and practices of university students. Design: A quasi-experimental design. Setting: Faculty of Nursing, Kafr elsheikh University. Sampling: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…This result in the same line with a study done in Saudi Arabia by Almulhim ,(2021) (69) who stated that more than one quarter of the studied subjects had good awareness level about climate change at posttest. Also, Ghazy & Fathy, (2023) (37) in Egypt reported that significant improvement in most aspects of studied sample' awareness about climate change after the program application. Additionally another studies conducted in Italy by Mebane et al, (2023) (70) and in Philippines by Adlit et al, (2023) (71) who stated that climate change education intervention improve the studied sample awareness level.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…This result in the same line with a study done in Saudi Arabia by Almulhim ,(2021) (69) who stated that more than one quarter of the studied subjects had good awareness level about climate change at posttest. Also, Ghazy & Fathy, (2023) (37) in Egypt reported that significant improvement in most aspects of studied sample' awareness about climate change after the program application. Additionally another studies conducted in Italy by Mebane et al, (2023) (70) and in Philippines by Adlit et al, (2023) (71) who stated that climate change education intervention improve the studied sample awareness level.…”
Section: Resultsmentioning
confidence: 90%
“…Also, the same result was reinforced by Amin et al, (2023) (74) in Egypt who revealed that study subjects with satisfactory knowledge were four times more likely to perceive danger as higher than participants with insufficient knowledge (P = 0.000*). Last but not least, A study conducted by Ghazy, and Fathy, (2023) (37) in Egypt who revealed that there was a highly positive correlation between total participants' knowledge score level &attitudes and total daily life practices (at p < 0.001). This result can be justified by that the greater the knowledge regarding climate change , the more the elderly demonstrate satisfactory practices and having positive attitude toward adaptation with climate change and its effects on their health.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Overall, the implemented CF awareness program directly affected students' decision-making for a de-carbonization lifestyle. The Egyptian study of Ghazy and Fathy (2023) (36), detected a highly significant statistical difference between pre and post-program regarding CC indoor and outdoor daily life practices.…”
Section: Discussionmentioning
confidence: 97%